Code-Switching in Selling and Buying at Segiri Market Samarinda, East Kalimantan: a Sociolinguistics Study - Islamiah Bastiar; Sri Marmanto; Sumarlam Sumarlam (Lingua Cultura, 2018)
The purposes of this research were (1) to describe the form of the code-switching in selling and buying at Segiri market Samarinda, East Kalimantan, and (2) to describe factors of code-switching in selling and buying at Segiri market Samarinda, East Kalimantan. The method used in this research was descriptive qualitative and employed a sociolinguistics study in the form of Poplack approach. Data sources of this research were activities and informants. Meanwhile, the type of data was the form of speech in the conversation. In collecting data, (1) observation, (2) field notes, (3) recording, and (4) interviews were used. In analyzing data, Miles and Huberman interactive analysis and Dell Hymes, ethnography communication method was used. The result of this research shows that (1) Form of the code-switching in selling and buying at Segiri market Samarinda, East Kalimantan are (a) tag switching consists of 21 data, and (b) inter-sentential consists of 41 data. The data is taken from Indonesian language, Banjar language, Kutai language, Java language, and Bugis language, and (2) Factors of community language, culture, tribe, and environment existing in Segiri market Samarinda, East Kalimantan also influences the way of code-switching in selling and buying transaction at Segiri market Samarinda, East Kalimantan.